Effect of vestibular rehabilitation on trunk kinetic and kinematic parameters in patients with multiple sclerosis - Riham Ali Mohamed; Saied Mohamed Ibrahim; Bassam Ahmed Nabil; Ahmed Magdy Alshimy (Termedia Publishing House, 2024)
Purpose To investigate the effect of the Cawthorne Cooksey exercise protocol on trunk kinetic and kinematic parameters in MS patients. Methods Using a randomised controlled study design, 30 ambulatory patients with MS (aged 35-55 years) with relapsing/ remitting disease, hemiparesis, and minimal disability were recruited. Patients were split into two equal groups to undergo four weeks of vestibular rehabilitation. Group I received conventional vestibular rehabilitation along with the Cawthorne Cooksey exercise protocol, and group II (control group) received only conventional vestibular rehabilitation. Patients were assessed using an isokinetic dynamometer (average power, acceleration, and deceleration time) before and after the treatment. Results The current study found that there was a significant improvement in the trunk flexors' average power and a decrease (enhancement) in the acceleration and deceleration times after the treatment (p < 0.05). The effect was more pronounced in group I than in group II. Conclusions Cawthorne Cooksey exercise protocol may be an effective way to help people with MS improve their dynamic trunk stability by facilitating trunk movements and muscle power.